Does cytomegalovirus infection contribute to socioeconomic disparities in all-cause mortality?. (September 2016) - Feinstein, Lydia; Douglas, Christian E; Stebbins, Rebecca C; Pawelec, Graham; Simanek, Amanda M.; Aiello, Allison E
Highlights: Low socioeconomic status (SES) is associated with increased mortality in the US. CMV seropositivity is associated with increased mortality in older age. Low SES is associated with increased prevalence of CMV independent of age. CMV partially mediates the association between SES and mortality as individuals age. Abstract: The social patterning of cytomegalovirus (CMV) and its implication in aging suggest that the virus may partially contribute to socioeconomic disparities in mortality. We used Cox regression and inverse odds ratio weighting to quantify the proportion of the association between socioeconomic status (SES) and all-cause mortality that was attributable to mediation by CMV seropositivity. Data were from the National Health and Nutrition Examination Survey (NHANES) III (1988–1994), with mortality follow-up through December 2011. SES was assessed as household income (income-to-poverty ratio ≤1.30; >1.30 to ≤1.85; >1.85 to ≤3.50; >3.50) and education (high school). We found strong associations between low SES and increased mortality: hazard ratio (HR) 1.80; 95% confidence interval (CI): 1.57, 2.06 comparing the lowest versus highest income groups and HR 1.29; 95% CI: 1.13, 1.48 comparing high school education. 65% of individuals were CMV seropositive, accounting for 6–15% of the SES-mortality associations. Age modified the associations between SES, CMV, and mortality, with CMV more strongly associated with mortality in older individuals. Our findings suggest that cytomegalovirus may partially contribute to persistent socioeconomic disparities in mortality, particularly among older individuals.